Pengaruh Kredit Mikro Terhadap Konsumsi Rumah Tangga Miskin Di Sumatera Barat - natasya putri; Isra Yeni (Universitas Negeri Padang, 2025)
This research examines the impact of access to microcredit and socio-economic characteristics on the consumption of poor households in Sumatera Barat using data from SUSENAS 2020 and multiple linear regression with robust standard errors. The results show that microcredit has a significant negative effect on consumption, presumably due to ineffective utilization and debt burden. Conversely, employment status, education, gender of the household head, number of members, and urban residency have a significant positive impact, while age has a negative effect. The findings emphasize the importance of a comprehensive approach that includes credit assistance, economic empowerment, and contextual policies to sustainably improve the well-being of poor households.